On the weighted boundary value problem for systems of degenerate ordinary differential equations - Rutkauskas, Stasys; Saburov, Igor (Lietuvos matematikos rinkinys, 2010)
A system of ordinary second order linear equations with a singular point is considered. The aim of this work is such that the system of eigenvectors of the matrix that couples the system of equations is not complete. That implies a matter of the statement of a weighted boundary value problem for this system. The well-posed boundary value problem is proposed in the article. The existence and uniqueness of the solution is proved.
Keywords: systems of the ordinary differential equations; irregular singularity; weighted boundary value problems